2021
DOI: 10.1002/celc.202101366
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lithium Tungstate on the Densification and Conductivity of Phosphate Lithium‐Ion Conductors

Abstract: Phosphate lithium‐ion conductors are outstanding electrolyte materials for solid‐state lithium batteries. As polycrystalline ceramics, they must be sintered at high temperatures. Lithium tungstate Li2WO4 (LWO) is reported for the first time as an effective sintering aid to reduce the sintering temperature for one of the most common solid‐state lithium‐ion conductors, Li1.5Al0.5Ti1.5(PO4)3 (LATP). While densification of LATP without sintering aids requires temperatures of at least 950 °C to obtain a relative de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…LWO, a material with a low melting temperature of 742 °C, has already been recognized as a very efficient sintering aid for densifying pure LATP, lowering the sintering temperature by more than 100 °C. 31 In this work, we show that LWO can also be added to the composite cathode, lowering the sintering temperature without affecting the phase composition of the LATP and LFP materials and resulting in mechanically stable, self-supporting cathodes with a smooth, homogeneous surface. The advantages of the optimized cathode microstructure are demon-strated in cell fabrication, which enables the deposition of a thin polymer separator layer without a supporting ceramic sheet 15 and a cell assembly that operates with lithium metal anodes without short-circuiting.…”
Section: Introductionmentioning
confidence: 76%
“…LWO, a material with a low melting temperature of 742 °C, has already been recognized as a very efficient sintering aid for densifying pure LATP, lowering the sintering temperature by more than 100 °C. 31 In this work, we show that LWO can also be added to the composite cathode, lowering the sintering temperature without affecting the phase composition of the LATP and LFP materials and resulting in mechanically stable, self-supporting cathodes with a smooth, homogeneous surface. The advantages of the optimized cathode microstructure are demon-strated in cell fabrication, which enables the deposition of a thin polymer separator layer without a supporting ceramic sheet 15 and a cell assembly that operates with lithium metal anodes without short-circuiting.…”
Section: Introductionmentioning
confidence: 76%
“…As a result of the comparison of the impurity removal time during the calcination process, it was found that the impurity phase did not appear in the LA_900 °C sample, from which the impurities were sufficiently removed. However, the LSC_900 °C and LWC_900 °C samples were found to contain small amounts of the LiTiPO 5 impurity phase, which has the potential to reduce the ionic conductivity, as shown in Figure d …”
Section: Resultsmentioning
confidence: 99%
“…However, the LSC_900 °C and LWC_900 °C samples were found to contain small amounts of the LiTiPO 5 impurity phase, which has the potential to reduce the ionic conductivity, as shown in Figure 2d. 45 As all samples were crystallized and the peaks were clearly distinguishable, the crystallinity of the samples was confirmed by two methods. The first method estimated the crystallinity based on the angle of XRD reflection expressed as the full width at half maximum (fwhm) of the XRD diffraction peak, while the second method estimated crystallinity based on the area of the XRD peak using eq 1.…”
Section: Resultsmentioning
confidence: 99%
“…The ionic conductivity of MAUST–LATP is 0.10 mS cm −1 , and the MAUST–LLZTO‐based lithium symmetric battery demonstrates good cycle stability over 5000 h at a current density of 0.1 mA cm −2 . The other scheme proposes that the addition of some sintering aids like Li 2 O, [ 67 ] Li 2 B 4 O 7 , [ 68 ] TeO 2 , [ 69 ] LiF, [ 70 ] and Li 2 WO 4 [ 71 ] can improve the ionic conductivity while reducing the sintering temperature. Usually, sintering aids reduce the activation energy of grain boundary lithium migration and increase the density of LATP [ 72 ] to boost electrical conductivity.…”
Section: Crystal Structure and Lithium‐ion Migration Channel And Key ...mentioning
confidence: 99%